Activities of the FGBI"ARRIAH"branch in the Republic of Crimea - S. I. Danilchenko; Ye. S. Kuzina; I. V. Borodkina (Ветеринария сегодня, 2018)
The information on the establishment of the FGBI «ARRIAH» Branch in the Republic of Crimea and stages of its development is given in the paper. Some aspects of its activities are under review and obtained results are analyzed.